Validity of problem-based learning tools with the steam approach to improve student learning outcomes on thermodynamics material - Sarmila B. Ali; Mursalin Mursalin; Trisnawaty Junus Buhungo (Jurnal Pijar Mipa, 2023)
The purpose of this research is to describe the level of validity of learning devices that use problem-based learning models with the STEAM approach to improve student learning outcomes in thermodynamics material. This research is a type of research and development (R&D). This research was conducted in class XI IPA I SMA Negeri 1 Limboto Barat, Kec. Limboto Barat, Kab. Gorontalo for the 2022/2023 academic year. This study uses the ADDIE development model: analysis, design, development, implementation, and evaluation. The results of this study indicate that learning tools that use the problem-based learning model with the STEAM approach are declared valid and suitable for use in the learning process. It can be seen from the validation results which show that the average validation of the developed learning tools obtains very valid criteria.